THE LEARNING HABITS OF MERCHANT MARINE’S CADETS IN INCREASING SPEAKING ABILITY: THE EXPERIENCE FROM SUCCESSFUL CADETS - Maru, Mister Gidion; Najoan, Violetta (SoCul: International Journal of Research in Social Cultural Issues, 2025)
The primary aim of the current study is to explore the learning habits of successful cadets in increasing speaking ability. A qualitative design is applied in this study. To collect the data, a semi-structured interview was conducted. The respondents are from Merchant Marine Polytechnic of North Sulawesi. They are the cadets who accepted a scholarship by prestigious shipping company named PT. Samudera Indonesia. The data are analyzed in three stages (organization, description, and interpretation). The research findings showed how did the cadets learn for their successful language acquisition particularly in increasing speaking ability. It consists of regular practice (self-talk), speaking with friends and teacher (Peer – feedback), engaging with media (watching movie, Vlogs and English lesson in you tube), the utilizing of technology (speaking with Ai and Chat GPT), singing, and note taking. Overall, consistent study habits and self-reflection play a key role in the development of language skills, which has an important influence on future approaches to language education and learning. Furthermore, the findings provide the strategy mostly practiced by the cadets. There are watching video and pairing or peer – feedback that become the dominant strategies in used by the cadets. It is clearly showing the strategies that become the habit of the cadets. Moreover, it is found out that the learning habit shaped learners to face challenges, develop their own strategies and regular practices to ensure success in language acquisition particularly in speaking.